Comparison of Risk Factor Control in the Year After Discharge for Ischemic Stroke Versus Acute Myocardial Infarction. Issue 2 (February 2018) - Bravata, Dawn M.; Daggy, Joanne; Brosch, Jared; Sico, Jason J.; Baye, Fitsum; Myers, Laura J.; Roumie, Christianne L.; Cheng, Eric; Coffing, Jessica; Arling, Greg
Abstract : Background and Purpose—: The Veterans Health Administration has engaged in quality improvement to improve vascular risk factor control. We sought to examine blood pressure (<140/90 mm Hg), lipid (LDL [low-density lipoprotein] cholesterol <100 mg/dL), and glycemic control (hemoglobin A1c <9%), in the year post-hospitalization for acute ischemic stroke or acute myocardial infarction (AMI). Methods—: We identified patients who were hospitalized (fiscal year 2011) with ischemic stroke, AMI, congestive heart failure, transient ischemic attack, or pneumonia/chronic obstructive pulmonary disease. The primary analysis compared risk factor control after incident ischemic stroke versus AMI. Facilities were included if they cared for ≥25 ischemic stroke and ≥25 AMI patients. A generalized linear mixed model including patient- and facility-level covariates compared risk factor control across diagnoses. Results—: Forty thousand two hundred thirty patients were hospitalized (n=75 facilities): 2127 with incident ischemic stroke and 4169 with incident AMI. Fewer stroke patients achieved blood pressure control than AMI patients (64%; 95% confidence interval, 0.62–0.67 versus 77%; 95% confidence interval, 0.75–0.78; P <0.0001). After adjusting for patient and facility covariates, the odds of blood pressure control were still higher for AMI than ischemic stroke patients (odds ratio, 1.39; 95% confidence interval, 1.21–1.51). There were no statistical differences for AMI versus stroke patients in hyperlipidemia ( P =0.534). Among patients with diabetes mellitus, the odds of glycemic control were lower for AMI than ischemic stroke patients (odds ratio, 0.72; 95% confidence interval, 0.54–0.96). Conclusions—: Given that hypertension control is a cornerstone of stroke prevention, interventions to improve poststroke hypertension management are needed. Abstract : Supplemental Digital Content is available in the text.